Decentralization of solid waste management services in rural Lebanon: Barriers and opportunities. Issue 6 (June 2020) - Abed Al Ahad, Mary; Chalak, Ali; Fares, Souha; Mardigian, Patil; Habib, Rima R
Rapid urbanization, closure of dumps, and insufficient infrastructure funding in Lebanon have resulted in improper municipal solid waste management (MSWM), creating a continuing trash crisis in recent years. In Beirut and Mount Lebanon, MSWM was carried out in centralized waste processing and disposal facilities operated by the government. The trash crisis and failure of the centralized system prompted several municipal authorities to decentralize MSWM by establishing local facilities, paid by the council taxes charged to beneficiary households. To study the feasibility of decentralized MSWM, a survey of 228 households in a rural village in Lebanon explored households' willingness to pay (WTP) for a local MSWM service. For data analysis, a multivariate Tobit model was used to examine the determinants of the WTP amount. Results showed that 79% of surveyed households in the studied village were willing to support local MSWM improvements by contributing an average yearly fee of US48, representing a 30% increase in their current council taxes. Analysis showed a significant positive association between the WTP amount and the household monthly income level, the residents perceived needs for urgency to act on solid waste management, and the households' responsibility to be involved in MSWM. An interview with the municipality mayor later revealed that financial, technical, and land resources are lacking to enable consideration of a decentralized project for MSWM in the village. Municipalities in rural areas have limited resources and are unable to sustain a decentralized MSWM service unless adjacent towns join effort in supporting and financing MSWM initiatives.